Regulation of normal human polyrnorphonuclear leucocytes by carnitine - Andrea Fattorossi; Roberto Biselli; Anna Casciaro; Sonia Tzantzoglou; Claudio de Simone (Mediators of Inflammation)
The effect of carnitine, a drug that plays an essential role in mitochondria metabolism, on some of the most important human polymorphonuclear leucocytes (PMN) activation steps including modulation of adhesion molecule density, reactive oxygen species production, and tumour necrosis factor-α (TNFα) production was investigated. The capability of carnitine in protecting PMN from deter ioration on storage was also studied. Data shows that carnitine exerts considerable effects on all PMN functions investigated. Although the ultimate effect was often donor dependent, TNFα production was exceptional in that carnitine was able to consistently reduce TNFα production in Staphylococcus aureus stimulated PMN in a clear dose-dependent fashion. It is concluded that carnitine may represent a useful active agent in situations characterized by PMN mobilization/activation.